The THE EFFECTIVENESS OF USING SHORT STORY TO TEACH SPEAKING SKILL TO THE ELEVENTH GRADE STUDENTS AT SENIOR HIGH SCHOOL 1 MUARA BELITI: THE EFFECTIVENESS OF USING SHORT STORY TO TEACH SPEAKING SKILL TO THE ELEVENTH GRADE STUDENTS AT SENIOR HIGH SCHOOL 1 MUARA BELITI - Rico, anita olivia; Dewi syafitri; Hamdan (Lingustic, Literature and English Education, 2024)
This research aimed to prove significantly effective or not to use short story in teaching speaking skill. This research used a pre-experimental design with one group pre-test and post-test. The population was all of the eleventh grade students of SMA Negeri 1 Muara Beliti with consist that 131 students. The sampling technique used cluster random sampling with method of lottery and the sample selected was XI IPA 2 class with consist 27 students. The data for this research were collected by used oral test. Technique for collecting the data was the researcher classifying individual score students and data collection. The researcher found that using Short Story to teach speaking skill to the eleventh grade students at senior high scholl 1 muara beliti was effective. It could be proved by the significant difference between the mean score in the pre-test and post-test. The mean score of the students in the pre-test was 4.60 and in the post-test was 7.30. the t-obtained was 17.66, it was higher than 2.056 as the critical value in t-table. Therefore, it was clearly stated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.